GE_GERICHTE P/6627/2018 vom 25. September 2019 - GE Cour de justice (2019)
CIRCULATION ROUTIÈRE(DROIT DE LA CIRCULATION ROUTIÈRE);FIXATION DE LA PEINE | LCR.90.al2; CPP.302.al3; aCP.34; aCP.42.al4; CP.106